Formation of health and fitness competencies of students in the process of physical education - Griban, G.; Kоbernyk, O.; Lytvynenko, A. (Montenegrin Sports Academy, 2020)
The technology of forming the health and fitness competencies of students of higher educational institutions is reviewed in the present paper, which includes designing the highly efficient educational activity of students and the management activity of a teacher with the principal orientation to the content and forms of the educational process in the personal-development technologies of training. The study aims to substantiate, implement, and verify the efficiency of the original methodical system of physical education of students of Ukrainian higher educational institutions. A total of 87 students, aged 18–22, including 46 males and 41 females, participated in the study. The research methods were conceptual-comparative analysis, questionnaires and surveys, pedagogical observations, expert assessments, testing, pedagogical experiment, and statistical methods. It has been determined that the original methodical system, implemented in the educational process of physical education, contributes to improving the quality of the physical education of students, forming highly-developed health and fitness competencies that are required during professional activity to maintain a high level of physical fitness and working capacity.
Keywords: physical education; methodical system; health and fitness competencies; students